Composite binder as well as preparation method and application thereof
By using a composite binder composed of fluorine-containing oligomers and esters to form a three-dimensional network structure, the problem of volume expansion of silicon negative electrode during the cycle of lithium-ion batteries is solved, and the circulation performance and Coulomb efficiency of the battery are improved.
Patent Information
- Application Number
- CN202311027510.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-15
- Publication Date
- 2025-02-21
AI Technical Summary
The huge volume expansion of silicon negative electrode during the circulation of lithium-ion batteries leads to various problems, and the prior art is difficult to effectively solve.
Provide a composite binder, including fluorine-containing oligomers and esters containing C=C bonds, to form a three-dimensional network structure under the action of a photoinitiator to prevent the volume expansion of the negative electrode during circulation. .
The negative electrode sheet prepared with this composite adhesive will not experience huge volume expansion during the circulation process, which improves the circulation performance and Coulomb efficiency of the lithium battery.
Smart Images

Figure CN119490796A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of materials, and in particular to a composite adhesive and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries are widely used in various electronic products and electric vehicles due to their inherent advantages of high energy density, long cycle life and low manufacturing cost. With the rapid development of electric vehicles and energy storage grids, the requirements for lithium battery energy density are getting higher and higher. Silicon materials are abundant in resources, with a theoretical specific capacity of more than 10 times that of graphite. The redox potential of lithium ions during lithium insertion / extraction is low, making it a promising material for the negative electrode of lithium-ion batteries.
[0003] However, the huge volume expansion (>300%) of silicon anode during the cycle process will cause a variety of problems. Recent studies have shown that high-performance silicon binders can effectively improve the cycling stability of electrodes. Therefore, in order to solve the practicality problem of silicon anode, it is particularly important to seek low-cost, high-performance silicon binders and their preparation technology. Summary of the invention
[0004] The purpose of the present invention is to provide a composite binder and its preparation method and application in view of the defects of the prior art. Under the action of a photoinitiator, the composite binder can form a three-dimensional network structure with good mechanical properties, so that the negative electrode plate prepared by using the composite binder will not undergo huge volume expansion during the cycle process.
[0005] To achieve the above objectives, in a first aspect, the present invention provides a composite adhesive, the composite adhesive comprising component A and component B;
[0006] The component A is a fluorine-containing oligomer; the component A is obtained by degrading a linear polymer elastomer containing fluorine atoms on the carbon atoms of the main chain or the side chain; the component B is an ester containing a C=C bond;
[0007] The mass ratio of component A to component B is 1:5 to 5:1;
[0008] The composite adhesive can form a three-dimensional network structure under the action of a photoinitiator.
[0009] Preferably, the linear polymer elastomer specifically includes: one or more of perfluororubber, fluoroether rubber, tetrafluoropropylene rubber or nitrosofluororubber.
[0010] Preferably, the esters specifically include: one or more of hydroxyethyl methacrylate, hydroxyethyl acrylate, hydroxypropyl methacrylate, ethylene glycol methacrylate, butyl methacrylate or methyl methacrylate.
[0011] In a second aspect, the present invention provides a method for preparing the composite adhesive described in any one of the first aspects above, the preparation method comprising:
[0012] Dissolving a linear polymer elastomer having fluorine atoms on carbon atoms of a main chain or a side chain in an acetone solution to prepare a solution with a preset molar concentration;
[0013] Adding benzyltrimethylammonium chloride and an aqueous hydrogen peroxide solution to the solution to obtain a mixed solution; wherein the benzyltrimethylammonium chloride and the linear polymer elastomer have a preset molar ratio;
[0014] Adding sodium hydroxide to the mixed solution, and stirring at room temperature until the mixed solution becomes transparent;
[0015] Adding a hydrochloric acid solution to the transparent mixed solution so that the transparent mixed solution generates a solid precipitate;
[0016] Filtering the solid precipitate to obtain a filtered mixed solution;
[0017] The filtered mixed solution is evaporated to dryness to obtain a fluorine-containing oligomer;
[0018] The fluorine-containing oligomer and the ester containing a C=C bond are mixed in an organic solvent according to a preset mass ratio to obtain a composite adhesive.
[0019] Preferably, the preset molar concentration is 0.5 mmol / L to 2 mmol / L; the preset molar ratio is 1:5 to 6:1; and the preset mass ratio is 1:5 to 5:1.
[0020] Preferably, the linear polymer elastomer includes one or more of perfluororubber, fluoroether rubber, tetrafluoropropylene rubber or nitrosofluororubber.
[0021] Preferably, the esters include one or more of hydroxyethyl methacrylate, hydroxyethyl acrylate, hydroxypropyl methacrylate, ethylene glycol methacrylate, butyl methacrylate or methyl methacrylate.
[0022] In a third aspect, the present invention provides a negative electrode plate for a lithium battery, wherein the negative electrode plate for a lithium battery comprises the composite binder described in any one of the first aspects above.
[0023] In a fourth aspect, the present invention provides a lithium battery, comprising the lithium battery negative electrode sheet described in the third aspect.
[0024] The embodiment of the present invention provides a composite binder and a preparation method and application thereof. Component A of the composite binder is a fluorine-containing oligomer; component B is an ester containing a C=C bond. By adjusting the mass ratio between component A and component B, a three-dimensional network structure with good mechanical properties can be formed under the action of a photoinitiator, so that the negative electrode plate prepared using the composite binder will not undergo huge volume expansion during the cycle process, thereby enabling the lithium battery prepared using the negative electrode plate to have better cycle performance and coulombic efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 A flow chart of a method for preparing a composite adhesive provided by an embodiment of the present invention;
[0026] Figure 2 Schematic diagram of the polymerization principle of the composite adhesive provided in an embodiment of the present invention. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments.
[0029] The composite binder provided in the embodiment of the present invention can be applied to the negative electrode plate of a lithium battery to reduce the volume expansion of the negative electrode during the cycle and improve the cycle stability of the electrode.
[0030] An embodiment of the present invention provides a composite adhesive, including component A and component B.
[0031] Wherein, component A is a fluorine-containing oligomer, which can be obtained by degradation of a linear polymer elastomer containing fluorine atoms on the carbon atoms of the main chain or the side chain. The linear polymer elastomer can specifically include: one or more of perfluororubber, fluoroether rubber, tetrafluoropropylene rubber or nitrosofluororubber. The molecular weight of component A is 10000 to 1000000. The mass ratio of component A to component B is 1:5 to 5:1, preferably 3:1.
[0032] Component B is an ester containing a C=C bond. The ester may specifically include one or more of hydroxyethyl methacrylate, hydroxyethyl acrylate, hydroxypropyl methacrylate, ethylene glycol methacrylate, butyl methacrylate or methyl methacrylate.
[0033] Therefore, by adjusting the mass ratio between component A and component B, further polymerization is carried out under the action of the photoinitiator, so that the composite binder can form a three-dimensional network structure with good mechanical properties, so that the negative electrode plate prepared using the composite binder will not undergo huge volume expansion during the cycle.
[0034] Figure 1 A flow chart of a method for preparing a composite adhesive provided by an embodiment of the present invention, such as Figure 1 As shown in, the present invention provides a method for preparing the above-mentioned composite adhesive, which specifically includes the following steps:
[0035] Step 110, dissolving a linear polymer elastomer containing fluorine atoms on carbon atoms of a main chain or a side chain in an acetone solution to prepare a solution with a preset molar concentration;
[0036] The linear polymer elastomer includes one or more of perfluororubber, fluoroether rubber, tetrafluoropropylene rubber or nitrosofluororubber. The preset molar concentration may be 0.5 mmol / L to 2 mmol / L.
[0037] Step 120, adding benzyltrimethylammonium chloride and an aqueous hydrogen peroxide solution to the solution to obtain a mixed solution; wherein the benzyltrimethylammonium chloride and the linear polymer elastomer have a preset molar ratio;
[0038] The preset molar ratio is 1:5 to 6:1. The molar ratio between hydrogen peroxide and the linear polymer elastomer can be 1:1 to 6:1.
[0039] Step 130, adding sodium hydroxide to the mixed solution, and stirring at room temperature until the mixed solution becomes transparent;
[0040] Specifically, the stirring method in this step is a conventional method to make the mixed solution become transparent, and the stirring equipment includes but is not limited to any one of a stirrer, an ultrasonic disperser, and a high-speed mixer. The molar ratio between sodium hydroxide and hydrogen peroxide can be 1:2 to 2:1.
[0041] Step 140, adding a hydrochloric acid solution to the transparent mixed solution, so that the transparent mixed solution generates a solid precipitate;
[0042] Wherein, the molar ratio between hydrochloric acid and sodium hydroxide can be 1:1 to 3:1.
[0043] Step 150, filtering the solid precipitate to obtain a filtered mixed solution;
[0044] Specifically, after the solid precipitate is filtered, the mixed solution is purified.
[0045] Step 160, evaporating and drying the filtered mixed solution to obtain a fluorine-containing oligomer;
[0046] Specifically, the filtered mixed solution can be placed in a rotary steam furnace for evaporation. When the solvent and water in the mixed solution are removed, a jelly is obtained. After that, the jelly is repeatedly washed and dried to obtain the fluorine-containing oligomer. The drying method includes: a combination of one or more methods of rotary evaporation drying, stirring drying, spray drying, vacuum drying, and post-filtration forced air drying. In this example, vacuum drying is specifically used.
[0047] The washing is repeated at least 4 times and the drying temperature is room temperature.
[0048] Step 170 , mixing the fluorine-containing oligomer and the ester containing a C═C bond in an organic solvent according to a preset mass ratio to obtain a composite adhesive.
[0049] The esters specifically include one or more of hydroxyethyl methacrylate, hydroxyethyl acrylate, hydroxypropyl methacrylate, ethylene glycol methacrylate, butyl methacrylate or methyl methacrylate. The preset mass ratio may be 1:5 to 5:1. The mixing process is mainly to graft the C=C bond to the fluorinated oligomer through an esterification reaction.
[0050] The composite binder can form a three-dimensional network structure with good mechanical properties under the action of the photoinitiator. Therefore, the composite binder can be used as a binder for the negative electrode sheet of a lithium battery and used in the preparation of the negative electrode sheet. It should be noted that if it is only used for the production of the negative electrode sheet, the photoinitiator can be added during the production process of the sheet.
[0051] Combine the following Figure 2 The polymerization process of the composite adhesive is briefly introduced. Benzyltrimethylammonium chloride, aqueous hydrogen peroxide solution and sodium hydroxide are added to a linear polymer elastomer solution in sequence and stirred until the solution becomes transparent. Then, a hydrochloric acid solution is added to cause the transparent solution to generate a precipitate, thereby obtaining a fluorinated oligomer component A with a molecular weight Mn of 2100-11000. Thereafter, an ester containing a C=C bond is added to component A, and the C=C bond is grafted to the fluorinated oligomer through an esterification reaction. Finally, through the action of a photoinitiator, the C=C bond is polymerized under the irradiation of ultraviolet light, thereby allowing the composite adhesive to form a stable three-dimensional network structure.
[0052] The following is a brief introduction to the process of preparing negative electrode sheets using the composite binder.
[0053] The negative electrode active material, the composite binder and the conductive agent are mixed in a certain mass ratio to obtain a mixed slurry;
[0054] Adding a photoinitiator to the mixed slurry, mixing evenly, and coating it on the negative electrode current collector, controlling the carbon silicon loading, irradiating it with ultraviolet light for a preset time, and fully polymerizing it to obtain a polymer;
[0055] The polymer is vacuum dried, taken out, and cut into discs as negative electrode sheets.
[0056] The photoinitiator specifically includes but is not limited to any one of photoinitiator 1173, photoinitiator 184, photoinitiator 907, photoinitiator TPO, photoinitiator TPO-L, methyl benzoylformate MBF, etc. The preset duration of illumination is 3 minutes to 10 minutes.
[0057] Among them, the negative electrode active material includes but is not limited to any one of carbon materials, tin-based negative electrode materials, silicon-based negative electrode materials, silicon-carbon composite materials, nano-oxide materials, and titanate negative electrode materials; carbon materials include any one of graphite, hard carbon, carbon fiber, petroleum coke, and mesophase carbon microspheres. The negative electrode current collector includes but is not limited to copper foil or titanium foil.
[0058] The conductive agent includes a solute and a solvent.
[0059] Wherein, the solute is a conductive salt, including any one of sodium perchlorate (NaClO4), sodium tetrafluoroborate (NaBF4), sodium hexafluorophosphate (NaPF6), sodium hexafluoroarsenate (NaAsF6), sodium trifluoroacetate (CF3COONa), lithium perchlorate (LiClO4), lithium hexafluorophosphate (LiPF6), lithium hexafluoroborate (LiBF6), and lithium hexafluoroarsenate (LiAsF6).
[0060] The solvent includes: one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinylene carbonate (VC), fluoroethylene carbonate (FEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), γ-butyrolactone (BL), methyl propionate (MP), methyl butyrate (MB), ethyl acetate (EA), ethyl propionate (EP), propyl propionate (PP), ethyl butyrate (EB), 1,3-dioxolane (DOL), ethylene glycol dimethyl ether (DME), diethylene glycol dimethyl ether (DEGDME), triethylene glycol dimethyl ether (TRGDME), tetraethylene glycol dimethyl ether (TEGDME), ethyl methanesulfonate (EMS) or dimethyl sulfoxide (DMSO).
[0061] It should be noted that the composite adhesive can also be used in the preparation of positive electrode sheets, but it is more effective when used in negative electrode sheets.
[0062] An embodiment of the present invention provides a lithium battery, which includes the above-mentioned lithium battery negative electrode plate.
[0063] The lithium battery is composed of the above-mentioned negative electrode sheet containing the composite binder, a separator, an electrolyte or a solid electrolyte, and a positive electrode sheet.
[0064] The diaphragm includes but is not limited to any one of a double-sided alumina diaphragm and a diaphragm containing a lithium ion solid electrolyte; the base film of the diaphragm includes any one of a polyolefin film, a non-woven fabric diaphragm, a fiber diaphragm, and a polyaramid diaphragm.
[0065] The positive electrode sheet mainly includes a positive electrode current collector, a positive electrode active material, a conductive agent and a binder.
[0066] The positive electrode current collector includes but is not limited to aluminum foil.
[0067] The positive electrode active material includes any one of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, nickel cobalt lithium manganese oxide ternary material, sodium cobalt oxide, vanadium pentoxide, and Prussian blue.
[0068] The conductive agent includes, but is not limited to, one or more of carbon black, carbon nanotubes, acetylene black, and Ketjen black.
[0069] The binder includes, but is not limited to, one or more of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, carboxymethyl cellulose, sodium carboxymethyl cellulose, polymethyl methacrylate, polyacrylate, polyacrylonitrile, styrene-butadiene rubber, polyvinyl alcohol, polytetrafluoroethylene, polyacrylamide, polyvinyl acetate, and polyurethane.
[0070] In order to better understand the technical solution provided by the present invention, the following uses a number of specific examples to illustrate the preparation process and characteristics of the negative electrode sheet using the composite binder of the present invention.
[0071] Example 1
[0072] The perfluororubber is dissolved in an acetone solution to prepare a solution with a preset molar concentration of 1 mmol / L; benzyltrimethylammonium chloride and hydrogen peroxide aqueous solution are added to the solution to obtain a mixed solution; wherein the molar ratio between benzyltrimethylammonium chloride and perfluororubber is 5:1; and the molar ratio between hydrogen peroxide and perfluororubber is 1:1. Sodium hydroxide is added to the mixed solution, and stirred at room temperature until the mixed solution becomes transparent; wherein the molar ratio between sodium hydroxide and hydrogen peroxide is 1:2. Hydrochloric acid solution is added to the transparent mixed solution so that the transparent mixed solution generates a solid precipitate; wherein the molar ratio between hydrochloric acid and sodium hydroxide is 1:1. The solid precipitate is filtered to obtain a filtered mixed solution; the filtered mixed solution is passed through a rotary steam furnace to remove the solvent and water, and then dried in a vacuum drying oven to obtain a fluorine-containing oligomer; the fluorine-containing oligomer and hydroxyethyl methacrylate are mixed uniformly in an organic solvent at a mass ratio of 1:1 to obtain a composite adhesive.
[0073] Silicon carbon material (450 mAh / g), composite binder, and conductive agent were mixed in a mass ratio of 93:5:2. At the same time, photoinitiator 1173 was added to the slurry to make the slurry evenly mixed and coated on copper foil to control the silicon carbon loading to 6 mg / cm 2 After irradiation with ultraviolet light for 3 minutes, the polymerized product was dried in a vacuum oven at 80°C for 8 hours. After drying, the product was taken out and cut into 12 mm diameter discs by a cutting machine as the negative electrode.
[0074] The positive electrode is a lithium sheet with a diameter of 12 mm.
[0075] The electrolyte was 1M LiPF6, EC / DEC (volume ratio 1:1) + 10% FEC. The polypropylene commercial separator was assembled in a glove box filled with argon (H2O < 0.01 ppm, O2 < 0.01 ppm).
[0076] The assembled batteries were subjected to a cycle performance test using a blue power test system with an operating voltage range of 0.005V-1.5V, followed by a long cycle test at 0.5C.
[0077] The test data of initial efficiency and capacity retention rate of the button cell prepared in this embodiment are shown in Table 1.
[0078] Example 2
[0079] Fluoroether rubber is dissolved in acetone solution to prepare a solution with a molar concentration of 1.2 mmol / L; benzyl trimethyl ammonium chloride and hydrogen peroxide aqueous solution are added to the solution to obtain a mixed solution; wherein the molar ratio between benzyl trimethyl ammonium chloride and fluoroether rubber is 2:1; and the molar ratio between hydrogen peroxide and fluoroether rubber is 1.5:1. Sodium hydroxide is added to the mixed solution and stirred at room temperature until the mixed solution becomes transparent; wherein the molar ratio between sodium hydroxide and hydrogen peroxide is 1:2. Hydrochloric acid solution is added to the transparent mixed solution so that the transparent mixed solution generates a solid precipitate; wherein the molar ratio between hydrochloric acid and sodium hydroxide is 1.2:1. The solid precipitate is filtered to obtain a filtered mixed solution; the filtered mixed solution is passed through a rotary steam furnace to remove the solvent and water, and then dried in a vacuum drying oven to obtain a fluorine-containing oligomer; the fluorine-containing oligomer and hydroxyethyl acrylate are mixed uniformly in an organic solvent at a mass ratio of 1:2 to obtain a composite adhesive.
[0080] Silicon carbon material (450 mAh / g), composite binder, and conductive agent were mixed in a mass ratio of 93:5:2. At the same time, photoinitiator 184 was added to the slurry to make the slurry evenly mixed and coated on copper foil to control the silicon carbon loading to 6 mg / cm 2 After being irradiated with ultraviolet light for 5 minutes, the polymerized product was dried in a vacuum oven at 70°C for 8 hours. After being dried, the product was taken out and cut into 12 mm diameter discs by a cutting machine to serve as the negative electrode.
[0081] The positive electrode, electrolyte and test conditions remain the same as in Example 1.
[0082] The test data of initial efficiency and capacity retention rate of the button cell prepared in this embodiment are shown in Table 1.
[0083] Example 3
[0084] Dissolve tetrafluoroethylene rubber in acetone solution to prepare a solution with a molar concentration of 2 mmol / L; add benzyl trimethyl ammonium chloride and hydrogen peroxide aqueous solution to the solution to obtain a mixed solution; wherein the molar ratio between benzyl trimethyl ammonium chloride and tetrafluoroethylene rubber is 1:1; and the molar ratio between hydrogen peroxide and tetrafluoroethylene rubber is 2:1. Add sodium hydroxide to the mixed solution and stir at room temperature until the mixed solution becomes transparent; wherein the molar ratio between sodium hydroxide and hydrogen peroxide is 1.2:1. Add hydrochloric acid solution to the transparent mixed solution so that the transparent mixed solution generates a solid precipitate; wherein the molar ratio between hydrochloric acid and sodium hydroxide is 1.5:1. Filter the solid precipitate to obtain a filtered mixed solution; remove the solvent and water from the filtered mixed solution through a rotary steam furnace, and then dry it in a vacuum drying oven to obtain a fluorine-containing oligomer; mix the fluorine-containing oligomer and hydroxypropyl methacrylate in an organic solvent at a mass ratio of 1:3 to obtain a composite adhesive.
[0085] Silicon carbon material (450 mAh / g), composite binder, and conductive agent were mixed in a mass ratio of 93:5:2. At the same time, photoinitiator 907 was added to the slurry to make the slurry evenly mixed and coated on copper foil to control the silicon carbon loading to 6 mg / cm 2 After being irradiated with ultraviolet light for 5 minutes, the polymerized product was dried in a vacuum oven at 70°C for 8 hours. After being dried, the product was taken out and cut into 12 mm diameter discs by a cutting machine to serve as the negative electrode.
[0086] The positive electrode, electrolyte and test conditions remain the same as in Example 1.
[0087] The test data of initial efficiency and capacity retention rate of the button cell prepared in this embodiment are shown in Table 1.
[0088] Example 4
[0089] Dissolve the nitroso fluororubber in an acetone solution to prepare a solution with a molar concentration of 0.8 mmol / L; add benzyl trimethyl ammonium chloride and hydrogen peroxide aqueous solution to the solution to obtain a mixed solution; wherein the molar ratio between benzyl trimethyl ammonium chloride and nitroso fluororubber is 4:1; and the molar ratio between hydrogen peroxide and nitroso fluororubber is 3:1. Add sodium hydroxide to the mixed solution and stir at room temperature until the mixed solution becomes transparent; wherein the molar ratio between sodium hydroxide and hydrogen peroxide is 1.5:1. Add hydrochloric acid solution to the transparent mixed solution so that the transparent mixed solution generates a solid precipitate; wherein the molar ratio between hydrochloric acid and sodium hydroxide is 2:1. Filter the solid precipitate to obtain a filtered mixed solution; remove the solvent and water from the filtered mixed solution through a rotary steam furnace, and then dry it in a vacuum drying oven to obtain a fluorine-containing oligomer; mix the fluorine-containing oligomer and hydroxypropyl methacrylate in an organic solvent at a mass ratio of 1:3 to obtain a composite adhesive.
[0090] Silicon carbon material (450 mAh / g), composite binder, and conductive agent were mixed in a mass ratio of 93:5:2. At the same time, photoinitiator 1173 was added to the slurry to make the slurry evenly mixed and coated on copper foil to control the silicon carbon loading to 6 mg / cm 2 After being irradiated with ultraviolet light for 8 minutes, the polymerized product was dried in a vacuum oven at 60°C for 8 hours. After being dried, the product was taken out and cut into 12 mm diameter discs by a cutting machine to serve as the negative electrode.
[0091] The positive electrode, electrolyte and test conditions remain the same as in Example 1.
[0092] The test data of initial efficiency and capacity retention rate of the button cell prepared in this embodiment are shown in Table 1.
[0093] Example 5
[0094] Fluoroether rubber is dissolved in acetone solution to prepare a solution with a molar concentration of 1.5 mmol / L; benzyl trimethyl ammonium chloride and hydrogen peroxide aqueous solution are added to the solution to obtain a mixed solution; wherein the molar ratio between benzyl trimethyl ammonium chloride and fluoroether rubber is 1:2; and the molar ratio between hydrogen peroxide and fluoroether rubber is 3.5:1. Sodium hydroxide is added to the mixed solution and stirred at room temperature until the mixed solution becomes transparent; wherein the molar ratio between sodium hydroxide and hydrogen peroxide is 1:2. Hydrochloric acid solution is added to the transparent mixed solution so that the transparent mixed solution generates a solid precipitate; wherein the molar ratio between hydrochloric acid and sodium hydroxide is 2.5:1. The solid precipitate is filtered to obtain a filtered mixed solution; the filtered mixed solution is passed through a rotary steam furnace to remove the solvent and water, and then dried in a vacuum drying oven to obtain a fluorine-containing oligomer; the fluorine-containing oligomer and ethylene glycol methacrylate are mixed uniformly in an organic solvent at a mass ratio of 1:5 to obtain a composite adhesive.
[0095] Silicon carbon material (450 mAh / g), composite binder, and conductive agent were mixed in a mass ratio of 93:5:2. At the same time, photoinitiator TPO was added to the slurry to make the slurry evenly mixed and coated on copper foil to control the silicon carbon loading to 6 mg / cm 2 After 10 minutes of ultraviolet irradiation, the polymerized film was dried in a vacuum oven at 80°C for 6 hours. After drying, the film was taken out and cut into 12 mm diameter discs by a cutting machine as the negative electrode.
[0096] The positive electrode, electrolyte and test conditions remain the same as in Example 1.
[0097] The test data of initial efficiency and capacity retention rate of the button cell prepared in this embodiment are shown in Table 1.
[0098] Example 6
[0099] Dissolve tetrafluoroethylene rubber in acetone solution to prepare a solution with a molar concentration of 1 mmol / L; add benzyltrimethylammonium chloride and hydrogen peroxide aqueous solution to the solution to obtain a mixed solution; wherein the molar ratio between benzyltrimethylammonium chloride and tetrafluoroethylene rubber is 1:4; and the molar ratio between hydrogen peroxide and tetrafluoroethylene rubber is 4:1. Add sodium hydroxide to the mixed solution and stir at room temperature until the mixed solution becomes transparent; wherein the molar ratio between sodium hydroxide and hydrogen peroxide is 0.6:1. Add hydrochloric acid solution to the transparent mixed solution so that the transparent mixed solution generates a solid precipitate; wherein the molar ratio between hydrochloric acid and sodium hydroxide is 2:1. Filter the solid precipitate to obtain a filtered mixed solution; remove the solvent and water from the filtered mixed solution through a rotary steam furnace, and then dry it in a vacuum drying oven to obtain a fluorine-containing oligomer; mix the fluorine-containing oligomer and ethylene glycol methacrylate in an organic solvent at a mass ratio of 2:1 to obtain a composite adhesive.
[0100] Silicon carbon material (450 mAh / g), composite binder, and conductive agent were mixed in a mass ratio of 93:5:2. At the same time, photoinitiator TPO was added to the slurry to make the slurry evenly mixed and coated on copper foil to control the silicon carbon loading to 6 mg / cm 2 After 10 minutes of ultraviolet irradiation, the polymerized film was dried in a vacuum oven at 80°C for 6 hours. After drying, the film was taken out and cut into 12 mm diameter discs by a cutting machine as the negative electrode.
[0101] The positive electrode, electrolyte and test conditions remain the same as in Example 1.
[0102] The test data of initial efficiency and capacity retention rate of the button cell prepared in this embodiment are shown in Table 1.
[0103] Example 7
[0104] Dissolve the nitroso fluororubber in an acetone solution to prepare a solution with a molar concentration of 1.5 mmol / L; add benzyl trimethyl ammonium chloride and hydrogen peroxide aqueous solution to the solution to obtain a mixed solution; wherein the molar ratio between benzyl trimethyl ammonium chloride and nitroso fluororubber is 1:5; and the molar ratio between hydrogen peroxide and nitroso fluororubber is 5:1. Add sodium hydroxide to the mixed solution and stir at room temperature until the mixed solution becomes transparent; wherein the molar ratio between sodium hydroxide and hydrogen peroxide is 0.8:1. Add hydrochloric acid solution to the transparent mixed solution so that the transparent mixed solution generates a solid precipitate; wherein the molar ratio between hydrochloric acid and sodium hydroxide is 1.5:1. Filter the solid precipitate to obtain a filtered mixed solution; remove the solvent and water from the filtered mixed solution through a rotary steam furnace, and then dry it in a vacuum drying oven to obtain a fluorine-containing oligomer; mix the fluorine-containing oligomer and ethylene glycol methacrylate in an organic solvent at a mass ratio of 2:1 to obtain a composite adhesive.
[0105] Silicon carbon material (450 mAh / g), composite binder, and conductive agent were mixed in a mass ratio of 93:5:2. At the same time, photoinitiator TPO was added to the slurry to make the slurry evenly mixed and coated on copper foil to control the silicon carbon loading to 6 mg / cm 2 After 10 minutes of ultraviolet irradiation, the polymerized film was dried in a vacuum oven at 80°C for 6 hours. After drying, the film was taken out and cut into 12 mm diameter discs by a cutting machine as the negative electrode.
[0106] The positive electrode, electrolyte and test conditions remain the same as in Example 1.
[0107] The test data of initial efficiency and capacity retention rate of the button cell prepared in this embodiment are shown in Table 1.
[0108] Example 8
[0109] The perfluororubber is dissolved in an acetone solution to prepare a solution with a molar concentration of 1 mmol / L; benzyltrimethylammonium chloride and hydrogen peroxide aqueous solution are added to the solution to obtain a mixed solution; wherein the molar ratio between benzyltrimethylammonium chloride and perfluororubber is 3:1; and the molar ratio between hydrogen peroxide and perfluororubber is 5.5:1. Sodium hydroxide is added to the mixed solution, and stirred at room temperature until the mixed solution becomes transparent; wherein the molar ratio between sodium hydroxide and hydrogen peroxide is 2:1. Hydrochloric acid solution is added to the transparent mixed solution so that the transparent mixed solution generates a solid precipitate; wherein the molar ratio between hydrochloric acid and sodium hydroxide is 1.8:1. The solid precipitate is filtered to obtain a filtered mixed solution; the filtered mixed solution is passed through a rotary steam furnace to remove the solvent and water, and then dried in a vacuum drying oven to obtain a fluorine-containing oligomer; the fluorine-containing oligomer and hydroxyethyl methacrylate are mixed uniformly in an organic solvent at a mass ratio of 3:1 to obtain a composite adhesive.
[0110] Silicon material (100nm), composite binder, and conductive agent were mixed in a mass ratio of 90:5:5. At the same time, photoinitiator 1173 was added to the slurry to make the slurry evenly mixed and coated on copper foil to control the silicon carbon loading to 1.5mg / cm 2 After irradiation with ultraviolet light for 7 minutes, the polymerized product was dried in a vacuum oven at 80°C for 6 hours. After drying, the product was taken out and cut into 12 mm diameter discs by a cutting machine as the negative electrode.
[0111] The positive electrode and electrolyte remain unchanged, the same as in Example 1. The test conditions are as follows:
[0112] The assembled batteries were subjected to a cycle performance test using a Blue Electric test system with an operating voltage range of 0.005V-1.5V, followed by a long cycle test at 0.2C.
[0113] The test data of initial efficiency and capacity retention rate of the button cell prepared in this embodiment are shown in Table 1.
[0114] Example 9
[0115] Dissolve tetrafluoroethylene rubber in acetone solution to prepare a solution with a molar concentration of 1 mmol / L; add benzyltrimethylammonium chloride and hydrogen peroxide aqueous solution to the solution to obtain a mixed solution; wherein the molar ratio between benzyltrimethylammonium chloride and tetrafluoroethylene rubber is 1:1; and the molar ratio between hydrogen peroxide and tetrafluoroethylene rubber is 6:1. Add sodium hydroxide to the mixed solution and stir at room temperature until the mixed solution becomes transparent; wherein the molar ratio between sodium hydroxide and hydrogen peroxide is 1.7:1. Add hydrochloric acid solution to the transparent mixed solution so that the transparent mixed solution generates a solid precipitate; wherein the molar ratio between hydrochloric acid and sodium hydroxide is 3:1. Filter the solid precipitate to obtain a filtered mixed solution; remove the solvent and water from the filtered mixed solution through a rotary steam furnace, and then dry it in a vacuum drying oven to obtain a fluorine-containing oligomer; mix the fluorine-containing oligomer and butyl methacrylate in an organic solvent at a mass ratio of 4:1 to obtain a composite adhesive.
[0116] Silicon material (100 nm), composite binder, and conductive agent were mixed in a mass ratio of 90:5:5. At the same time, photoinitiator 184 was added to the slurry to make the slurry evenly mixed and coated on copper foil to control the silicon carbon loading to 1.5 mg / cm 2 After irradiation with ultraviolet light for 9 minutes, the polymerized product was dried in a vacuum oven at 80°C for 6 hours. After drying, the product was taken out and cut into 12 mm diameter discs by a cutting machine to serve as the negative electrode.
[0117] The positive electrode and electrolyte remain unchanged, the same as in Example 1. The test conditions are as follows:
[0118] The assembled batteries were subjected to a cycle performance test using a Blue Electric test system with an operating voltage range of 0.005V-1.5V, followed by a long cycle test at 0.2C.
[0119] Example 10
[0120] Dissolve tetrafluoroethylene rubber in acetone solution to prepare a solution with a molar concentration of 0.5 mmol / L; add benzyl trimethyl ammonium chloride and hydrogen peroxide solution to the solution to obtain a mixed solution; wherein the molar ratio between benzyl trimethyl ammonium chloride and tetrafluoroethylene rubber is 6:1; and the molar ratio between hydrogen peroxide and tetrafluoroethylene rubber is 6:1. Add sodium hydroxide to the mixed solution and stir at room temperature until the mixed solution becomes transparent; wherein the molar ratio between sodium hydroxide and hydrogen peroxide is 1.7:1. Add hydrochloric acid solution to the transparent mixed solution so that the transparent mixed solution generates a solid precipitate; wherein the molar ratio between hydrochloric acid and sodium hydroxide is 3:1. Filter the solid precipitate to obtain a filtered mixed solution; remove the solvent and water from the filtered mixed solution through a rotary steam furnace, and then dry it in a vacuum drying oven to obtain a fluorine-containing oligomer; mix the fluorine-containing oligomer and butyl methacrylate in an organic solvent at a mass ratio of 5:1 to obtain a composite adhesive.
[0121] Silicon carbon material (450 mAh / g), composite binder, and conductive agent were mixed at a mass ratio of 90:5:5. At the same time, photoinitiator 184 was added to the slurry to make the slurry evenly mixed and coated on copper foil to control the silicon carbon loading to 1.5 mg / cm 2 After 10 minutes of ultraviolet irradiation, the polymerized film was dried in a vacuum oven at 80°C for 6 hours. After drying, the film was taken out and cut into 12 mm diameter discs by a cutting machine as the negative electrode.
[0122] The positive electrode and electrolyte remain unchanged, the same as in Example 1. The test conditions are as follows:
[0123] The assembled batteries were subjected to a cycle performance test using a Blue Electric test system with an operating voltage range of 0.005V-1.5V, followed by a long cycle test at 0.2C.
[0124] In order to better illustrate the effect of the embodiment of the present invention, the comparative example is compared with the above embodiment.
[0125] Comparative Example 1
[0126] Silicon carbon material (450mAh / g), binder polyvinylidene fluoride, and conductive agent were mixed in a mass ratio of 93:5:2, and the solvent was water. It was coated on copper foil and the silicon carbon loading was controlled to 6mg / cm 2 , dried in a vacuum drying oven at 80°C for 6 hours. After drying, the electrode was taken out and cut into discs with a diameter of 12 mm by a cutting machine to serve as the negative electrode.
[0127] The positive electrode is a lithium sheet with a diameter of 12 mm.
[0128] The electrolyte was 1M Li PF6, EC / DEC (volume ratio 1:1) + 10% FEC. The polypropylene commercial separator was assembled in a glove box filled with argon (H2O < 0.01 ppm, O2 < 0.01 ppm).
[0129] The assembled batteries were subjected to a cycle performance test using a blue power test system with an operating voltage range of 0.005V-1.5V, followed by a long cycle test at 0.5C.
[0130] The test data of initial efficiency and capacity retention rate of the button cell prepared in this embodiment are shown in Table 1.
[0131] Comparative Example 2
[0132] Silicon material (100nm), binder polyvinylidene fluoride, and conductive agent were mixed in a mass ratio of 90:5:5, and the solvent was water. It was coated on copper foil and the silicon carbon loading was controlled to be 1.5mg / cm 2 , dried in a vacuum drying oven at 80°C for 8 hours. After drying, the electrode was taken out and cut into discs with a diameter of 12 mm by a cutting machine to serve as the negative electrode.
[0133] The positive electrode is a lithium sheet with a diameter of 12 mm.
[0134] The electrolyte was 1M Li PF6, EC / DEC (volume ratio 1:1) + 10% FEC. The polypropylene commercial separator was assembled in a glove box filled with argon (H2O < 0.01 ppm, O2 < 0.01 ppm).
[0135] The assembled batteries were subjected to a cycle performance test using a blue power test system with an operating voltage range of 0.005V-1.5V, followed by a long cycle test at 0.5C.
[0136] The test data of initial efficiency and capacity retention rate of the button cell prepared in this embodiment are shown in Table 1.
[0137] Table 1 Test data of batteries assembled with binders prepared in Examples 1-9 and Comparative Examples 1 and 2
[0138] First week efficiency Specific capacity retention rate (50 cycles) Specific capacity retention rate (100 cycles) Example 1 87.78% 96.42% 91.78% Example 2 88.26% 97.18% 92.65% Example 3 87.45% 96.85% 91.57% Example 4 87.18% 97.44% 92.84% Example 5 88.15% 96.83% 92.02% Example 6 87.59% 96.55% 91.88% Example 7 88.44% 97.38% 93.08% Example 8 73.72% 77.75% 71.65% Example 9 75.48% 75.68% 70.08% Comparative Example 1 81.27% 92.1% 87.16% Comparative Example 2 68.47% 65.91% 42.19%
[0139] As shown in Table 1, compared with Comparative Example 1, the first-week efficiency (initial coulomb efficiency) of Examples 1-7 is increased by an average of about 6%, and the specific capacity retention rate after 50 and 100 cycles is also higher. Compared with Comparative Example 2, Examples 8 and 9 have higher first-week efficiency and higher specific capacity retention rate after 50 and 100 cycles. The above results show that the lithium battery with the negative electrode sheet prepared by the composite binder of the embodiment of the present invention has higher first-week efficiency and better cycle life. In addition, when the negative electrode active material is nano-silicon, the effect is more obvious.
[0140] The embodiment of the present invention provides a composite binder and a preparation method and application thereof. Component A of the composite binder is a fluorine-containing oligomer; component B is an ester containing a C=C bond. By adjusting the mass ratio between component A and component B, a three-dimensional network structure with good mechanical properties can be formed under the action of a photoinitiator, so that the negative electrode plate prepared using the composite binder will not undergo huge volume expansion during the cycle process, thereby enabling the lithium battery prepared using the negative electrode plate to have better cycle performance and coulombic efficiency.
[0141] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A composite adhesive, characterized in that: The composite binder comprises component A and component B; The component A is a fluorine-containing oligomer; the component A is obtained by degrading a linear polymer elastomer containing fluorine atoms on the carbon atoms of the main chain or the side chain; the component B is an ester containing a C=C bond; The mass ratio of component A to component B is 1:5 to 5:1; The composite adhesive can form a three-dimensional network structure under the action of a photoinitiator.
2. The composite adhesive according to claim 1, characterized in that: The linear polymer elastomer specifically includes: one or more of perfluororubber, fluoroether rubber, tetrafluoropropylene rubber or nitrosofluororubber.
3. The composite adhesive according to claim 1, characterized in that: The esters specifically include: one or more of hydroxyethyl methacrylate, hydroxyethyl acrylate, hydroxypropyl methacrylate, ethylene glycol methacrylate, butyl methacrylate or methyl methacrylate.
4. A method for preparing the composite adhesive according to any one of claims 1 to 3, the preparation method comprising: Dissolving a linear polymer elastomer having fluorine atoms on carbon atoms of a main chain or a side chain in an acetone solution to prepare a solution with a preset molar concentration; Adding benzyltrimethylammonium chloride and an aqueous hydrogen peroxide solution to the solution to obtain a mixed solution; wherein the benzyltrimethylammonium chloride and the linear polymer elastomer have a preset molar ratio; Adding sodium hydroxide to the mixed solution, and stirring at room temperature until the mixed solution becomes transparent; Adding a hydrochloric acid solution to the transparent mixed solution so that the transparent mixed solution generates a solid precipitate; Filtering the solid precipitate to obtain a filtered mixed solution; The filtered mixed solution is evaporated to dryness to obtain a fluorine-containing oligomer; The fluorine-containing oligomer and the ester containing a C=C bond are mixed in an organic solvent according to a preset mass ratio to obtain a composite adhesive.
5. The preparation method according to claim 4, characterized in that: The preset molar concentration is 0.5 mmol / L to 2 mmol / L; the preset molar ratio is 1:5 to 6:1; and the preset mass ratio is 1:5 to 5:
1.
6. The preparation method according to claim 4, characterized in that: The linear polymer elastomer includes: one or more of perfluororubber, fluoroether rubber, tetrafluoropropylene rubber or nitrosofluororubber.
7. The preparation method according to claim 4, characterized in that: The esters include one or more of hydroxyethyl methacrylate, hydroxyethyl acrylate, hydroxypropyl methacrylate, ethylene glycol methacrylate, butyl methacrylate or methyl methacrylate.
8. A negative electrode plate for a lithium battery, characterized in that: The negative electrode plate of the lithium battery comprises the composite binder as described in any one of claims 1 to 3 above.
9. A lithium battery, characterized in that: The lithium battery comprises the lithium battery negative electrode plate as described in claim 8 above.